Financial market prediction system with Evolino neural network and Delphi method - Maknickienė, Nijolė; Maknickas, Algirdas (Journal of Business Economics and Management, 2013)
Use of artificial intelligence systems in forecasting financial markets requires a reliable and simple model that would ensure profitable growth. The model presented in the paper combines Evolino recurrent neural networks with orthogonal data inputs and the Delphi expert evaluation method for its investment portfolio decision making process. A statistical study demonstrates the reliability of the model and describes its accuracy. Capabilities of the model are demonstrated using a trading simulation.